1987
DOI: 10.1111/j.1469-7610.1987.tb01767.x
|View full text |Cite
|
Sign up to set email alerts
|

Family Intervention With Bereaved Children

Abstract: This paper describes an intervention study carried out with 45 families (83 children) where one of the parents died, leaving a child or children under 16 years of age. The families were randomly assigned to treatment and control groups, the treatment group being seen by a family therapist for approximately six sessions within 3-5 months of bereavement. All the families were contacted approximately 1 year after and again 2 years after the bereavement and a structured interview was carried out, covering parental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
69
0
2

Year Published

1987
1987
2014
2014

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(72 citation statements)
references
References 23 publications
1
69
0
2
Order By: Relevance
“…77,90,91 Similarly, children with ID would also benefit if families were more open in communicating about their feelings following a loss. 92,93 Unfortunately, many parents find it difficult to communicate with children about death, especially when they themselves are dealing with the loss a spouse. There is abundant evidence for breakdowns in both factual/informational 77,94 and affective/emotional 95,96 communication surrounding the death of a parent, even when the surviving parent reports that he or she is aware of the importance of communication.…”
Section: Communicating About Lossmentioning
confidence: 99%
“…77,90,91 Similarly, children with ID would also benefit if families were more open in communicating about their feelings following a loss. 92,93 Unfortunately, many parents find it difficult to communicate with children about death, especially when they themselves are dealing with the loss a spouse. There is abundant evidence for breakdowns in both factual/informational 77,94 and affective/emotional 95,96 communication surrounding the death of a parent, even when the surviving parent reports that he or she is aware of the importance of communication.…”
Section: Communicating About Lossmentioning
confidence: 99%
“…There are few studies of the value of bereavement interventions. A review in 1990 identified four randomized studies, primarily addressing perinatal grief counselling (9,(20)(21)(22)(23). A search of MedLine from 1966 to 2002 produced no other citations.…”
Section: Discussionmentioning
confidence: 99%
“…Considerable clinical data and experience also support the finding that healthy adaptation to parental loss is more likely to occur when family relationships are characterized by sharing information and the open expression of anger, guilt, sadness, and feelings about the deceased. [13][14][15] Informing the children of a parent's condition and prognosis is one of the major challenges that families face. 16 Although much research has been conducted on how health care providers tell patients that they have life-threatening diagnoses and poor prognoses, 17,18 little is known about how parents tell their children that one parent is seriously ill or dying.…”
Section: Introductionmentioning
confidence: 99%